Analisis Faktor Yang Berhubungan Dengan Kecemasan Pasien Pre-Kateterisasi Jantung Di Rumah Sakit Panti Rapih Yogyakarta - Prabandari, Anna; Widyastuti, Chatarina Setya; Wardani, Yulia (I Care Jurnal Keperawatan STIKes Panti Rapih, 2022)
One of the diagnostic and intervention treatment in cardiovascular disease is cardiac catheterization. Cardiac catheterization is an invasive procedure, and every medical procedure, whether invasive or not, causes kind of emotional reactions for the patient. One such reaction is anxiety which usually occurs before medical treatment. The purpose of this study was to identify factors associated with cardiac pre-catheterization patient anxiety at Panti Rapih Hospital Yogyakarta. This is a quantitative descriptive correlative study with a cross-sectional approachment. The population were ACS (Acute Coronary Syndrome) patients who underwent cardiac catheterization from December 2020 to March 2021 at Panti Rapih Hospital. The sampling technique of this study was accidental-purposive gathered 25 respondents. Data collection methods: questionnaires and observation sheets. Results: factors associated with pre-catheterized cardiac patient anxiety were gender p-value = 0.017 and knowledge of procedures p-value = 0.000, which was not related to anxiety of pre-catheterized cardiac patients: level of education p-value = 0.522, family support p-value = 0.379, catheterization experience with p-value = 0.100 and waiting time p-value = 0.673. Suggestions for nursing are to provide education related to catheterization with attractive media and for further researchers to conduct similar research with qualitative methods.